ORGANIZING LEARNING ACTIVITIES AT SMP ISLAM AL-ULUM TERPADU MEDAN - Setiawan, Hasrian Rudi (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to describe the organization of learning activities at SMP Islam Al-Ulum Terpadu Medan. This study uses a qualitative research method with a phenomenological approach. Data collection techniques used are: observation, interviews, and documentation studies. Data analysis was carried out using techniques: selecting, presenting data, and drawing conclusions. The results of the study illustrate that the organization of learning activities at SMP Islam Al-Ulum Terpadu Medan is by arranging the learning of curriculum content in one span of time. This organization also includes managing the learning load in the curriculum structure, subject matter and study areas, study time arrangements, and the learning process. Thus, organizing student activities in improving the quality of graduates is carried out by establishing a division of tasks (authority) on the parties involved.